Professional Quality of Life and Changes in Spirituality Among VHA Chaplains: A Mixed Methods Investigation. Issue 3 (3rd July 2017) - McCormick, Wesley H.; Carroll, Timothy D.; Slagel, Brett A.; Drescher, Kent D.; Nieuwsma, Jason A.; Currier, Joseph M.
Abstract : A mixed method design was implemented to examine the spirituality and emotional well-being of Veterans Health Administration (VHA) chaplains and how potential changes in spirituality and emotional well-being may affect their professional quality of life. Four distinct categories of changes emerged from the narrative statements of a nationally representative sample of 267 VHA chaplains: (1) positive changes (e.g., increased empathy), (2) negative changes (e.g., dysthymic mood, questioning religious beliefs), (3) combination of positive and negative changes, and (4) no change (e.g., sustenance through spirituality or self-care). Most chaplains reported positive (37%) or no change (30%) in their spirituality and/or emotional well-being. However, quantitative analyses revealed that chaplains who reported negative changes endorsed greater burnout and secondary traumatic stress. Overall, these findings suggest VHA chaplains are predominantly spiritually resilient, but negative changes in the spiritual domain can occur, potentially increasing the risk of adverse changes in professional quality of life.